e-resilient-lowland: an e-learning toolkit to improve water control in West African rice producing countries - CGIAR Research Program on Rice (2019)
e-resilient-lowland is an e-learning toolkit to improve water control and climate resilience in inland valleys. Beneficiaries of the innovation are service providers who transfer the knowledge of inland valley development to farmers and the farmers themselves who can download the application and follow the easy-to-apply instructions for improved water control.